2006
DOI: 10.1158/1078-0432.ccr-05-2470
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Abundance of HLA Class II Presented Peptides in Primary Renal Cell Carcinomas

Abstract: Purpose: To elicit a long-lasting antitumor immune response, CD8+ and CD4 + Tcells should be activated. We attempted to isolate HLA-DR^presented peptides directly from dissected solid tumors, in particular from renal cell carcinoma, to identify MHC class II ligands from tumorassociated antigens (TAA) for their use in peptide-based immunotherapy. Experimental Design: Tumor specimens were analyzed by immunohistochemical staining for their HLA class II expression. HLA class II peptides were subsequently isolated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…Later, 55 peptides were sequenced from 9 human intestine samples from patients with inflammatory bowel disease (13). Recently, a large number of HLA class II-associated peptides have been identified from primary renal carcinoma samples (14).…”
Section: Lass II Mhcmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, 55 peptides were sequenced from 9 human intestine samples from patients with inflammatory bowel disease (13). Recently, a large number of HLA class II-associated peptides have been identified from primary renal carcinoma samples (14).…”
Section: Lass II Mhcmentioning
confidence: 99%
“…Peptide sequences were obtained by electrospray tandem MS using an LCQ ion trap mass spectrometer (Thermo Fisher Scientific) with a nanospray electrospray ionization (nESI) source (nESI-ion trap MS (ITMS)/MS from Protana A/S, Odense, Denmark), by a MALDI-TOF/TOF in a mass spectrometer (AB 4700 mass . Expression scores are based on immunofluorescence staining on cryostat sections as follows: ϩ, positive staining in Ͻ10% follicles (focal); ϩϩ, 10 -50% positive follicles (multifocal); ϩϩϩ, Ͼ50% positive follicles (generalized) (14).…”
Section: Peptide Sequencingmentioning
confidence: 99%
“…The most common ones observed in many tumors, such as lack of infiltration with cytotoxic lymphocytes or loss of MHC class I, do not explain the immune escape of human RCC satisfactorily: RCC tissues are generally strongly infiltrated by various types of immune cells that are considered to be associated with an effective immune response, notably dendritic cells, NK cells, and CD8 + T lymphocytes expressing MHC class I-restricted tumor-reactive TCRs (5-7, 11, 12). Moreover, renal tumors express MHC class I and class II molecules on the cell surface, and T cell epitopes are eluted from tumor tissues (13,14), indicating good Ag processing and presentation in situ. However, earlier studies analyzing NK cells (11) and T cells of RCC showed that infiltrating cytotoxic lymphocytes are functionally inactive but are able to gain function when cultured ex vivo (4,5,15), suggesting that inhibitory mechanisms act at the tumor site.…”
mentioning
confidence: 99%
“…In this respect promising results in phase II studies have been obtained by Immatics (www.immatics.com) . This technology consists in the vaccination of patients with multiple tumour-associated peptides (TUMAPs) that can be isolated from tumour specimens and identified by mass spectrometry (Dengjel et al, 2006). The most advanced product, IMA901, a combination of several TUMAPs for the treatment of renal cell carcinoma, completed a Europe-wide multi-center Phase II clinical trial and has recently commenced a Phase III trial.…”
Section: Peptide Vaccinesmentioning
confidence: 99%